Tingkat Kepatuhan Masyarakat dalam Pendaftaran Data Kependudukan di Kelurahan Tanjung Sari Kecamatan Medan Selayang Kota Medan - Fadhilla, Ayu; Novira, Nina (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2024)
This study aims to find out: (1) The level of community compliance in registering population data in Tanjung Sari Village (2) The reasons for compliance with population data registration in Tanjung Sari Village. This research was conducted in the Tanjung Sari Village, Medan Selayang District, Medan City in April-May 2023. The population in this study was all heads of households in the Tanjung Sari Village as many as 10,409 families with a sample determined by the Slovin formula so that 174 families were obtained. The data collection technique was carried out using a questionnaire. The data analysis technique was descriptive qualitative. The results showed that: (1) The level of compliance of the Tanjung Sari Village community in registering population data was quite good (61.8%) while those who did not comply because there was no time and was unnecessary (2) The most dominant reason for community compliance in registering population data was the community did not experience problems in registration and reasons for non-compliance due to the absence of witnesses and punishments, especially in the registration of certificates of adoption, divorce certificates and death certificates.